2022
DOI: 10.1038/s41467-022-28686-x
|View full text |Cite
|
Sign up to set email alerts
|

Overall photosynthesis of H2O2 by an inorganic semiconductor

Abstract: Artificial photosynthesis of H2O2 using earth-abundant water and oxygen is a promising approach to achieve scalable and cost-effective solar fuel production. Recent studies on this topic have made significant progress, yet are mainly focused on using  organic polymers. This set of photocatalysts is susceptible to potent oxidants (e.g. hydroxyl radical) that are inevitably formed during H2O2 generation. Here, we report an inorganic Mo-doped faceted BiVO4 (Mo:BiVO4) system that is resistant to radical oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(95 citation statements)
references
References 40 publications
1
93
1
Order By: Relevance
“…S3) show that the BiVO4 particles exhibit a decahedron structure with clear facets. Following previous studies, 18,19 the top/bottom and side facets are assigned to {010} reduction facets and {110} oxidation facets, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…S3) show that the BiVO4 particles exhibit a decahedron structure with clear facets. Following previous studies, 18,19 the top/bottom and side facets are assigned to {010} reduction facets and {110} oxidation facets, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Two electrons and two protons are consumed simultaneously to generate H 2 O 2 . This reaction pathway has now been found in various photocatalysts. g -C 3 N 4 is the first polymer photocatalyst to exhibit high selectivity (90%) toward photocatalytic H 2 O 2 production via the direct two-electron ORR pathway (Figure a) . Based on Raman and electron spin resonance (ESR) spectroscopic characterizations, it was shown that the high H 2 O 2 selectivity was attributed to the formation of 1,4-endoperoxide species on the heptazine structure (Figure b).…”
Section: Reaction Pathways Toward Overall Photosynthesis Of Hydrogen ...mentioning
confidence: 85%
“…The peaks centered at 780.6 eV and 796.3 eV could be ascribed to Co 3+ , while the peaks at 782.0 eV and 797.3 eV could be attributed to Co 2+ . 53,61,67 Thus, the mixed chemical states present in the Co species of the composites and the cocatalyst should be denoted as CoO x .…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…Considering the advantages of CoO x and Au, a dual-channel charge carrier transfer path could be established. [51][52][53] Moreover, combined with the features of extended interface contact areas and decreased charge transfer time, 2D BMO could further accelerate the migration of charge carriers. In a nutshell, we believe that the introduction of CoO x and Au on 2D BMO nanosheets provides an unprecedented opportunity to restrain the recombination of photogenerated electrons and holes.…”
Section: Introductionmentioning
confidence: 99%